Systemic glucocorticoids plus cyclophosphamide for acute exacerbation of idiopathic pulmonary fibrosis: a retrospective nationwide study - Aso, Shotaro; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Purpose: Mortality of acute exacerbation of idiopathic pulmonary fibrosis is high, and it remains unknown whether cyclophosphamide is an effective treatment for this condition. Objectives: This study compared the effects of cyclophosphamide combined with systemic glucocorticoids with those of systemic glucocorticoids alone. Methods: Using the Diagnosis Procedure Combination database in Japan, adult patients with idiopathic pulmonary fibrosis who had received high-dose methylprednisolone and mechanical ventilation at admission from July 1, 2010, to March 31, 2014, were identified. Instrumental variable analyses based on a hospital preference for cyclophosphamide were performed to compare in-hospital outcomes. Results: Eligible patients (n=1847) were divided into the methylprednisolone plus cyclophosphamide group (n=104) and the methylprednisolone alone group (n=1743). The results of an instrumental variable analysis detected no significant differences between the groups with respect to in-hospital mortality (odds ratio, 1.11; 95% confidence interval, 0.19-6.43), ventilator-free days (difference, 2.2; 95% confidence interval, −2.6 to 7.0). Conclusions: In a Japanese inpatient database study analyzing outcomes from patients with acute exacerbation idiopathic pulmonary fibrosis receiving systemic glucocorticoids, the addition of cyclophosphamide was not associated with improved in-hospital mortality and ventilator-free days.